Penguatan Kapasitas Guru SMK Melalui Implementasi Model Pembelajaran Berbasis Proyek (PjBL) - Anwar Basalamah; Sri Fajar Ayuningsih; Ahmad Junaedi Abas; Antonius Adi; Budi Riyanto (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
Project-Based Learning is an innovative learning method that is student-centered and utilizes the teacher as a motivator and facilitator. Students are directed to explore, assess, interpret, synthesize, and provide information in order to produce a variety of learning outcomes. The aim of Community Service activities with SMK Negeri 27 Jakarta teachers as target partners is to improve teacher skills in implementing this learning model. This study's research methodology is associated to approaches being used community service activities, particularly: (1) providing project-based learning materials to participants; (2) conducting pre- and post-tests to assess participants' comprehension of the material; (3) hands-on practical training so that participants can develop project-based learning programs for students and present them in training forums; and (4) discussion and evaluation. This activity resulted in a better comprehension of the subject and the creation of five project-based instructional materials with competency abilities in the sectors of tourism (accommodation and tourism service business), fashion design, catering, and beauty management.